PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PADA PT BUKIT ASAM TBK TAHUN 2014-2024 - Pasaribu, Harold Nathanael Hotasi; Ilham, Muhammad Arifin (Jurnal Akuntansi AKTIVA, 2026)
This research seeks to investigate the impact of Company Size and Leverage on Profitability at PT Bukit Asam Tbk during the period of 2014-2024. The data were analyzed through various stages utilizing descriptive statistical anal-ysis methods, multiple linear regression analysis tests, determination coefficient tests (R2), and hypothesis tests (t-tests), all processed with SPSS version 27. The findings of this research reveal that the Company Size variable does not have a significant effect on Profitability, and similarly, the Leverage variable also does not significantly affect Profitability.